Systems Thinking Creative Holim for Managers - Michael J. Jackson (John Wiley & Sons Ltd, 2003)
Complexity stems from the nature of problems. They rarely present themselves individually, but come related to other problems, in richly interconnected problem situations that are appropriately described by Russ AckoÂ¡ as â€˜messesâ€™. As a result, once you examine them, problems seem to get bigger and to involve more issues and stakeholders. Change is a product of our era. Organizations, if they are to remain viable, have to respond adroitly to constant shifts in their environments. Customers change their preferences over shorter time spans. Competition can be global and is often fuelled by the onward march of technological innovation. Governments impose new regulations. Transformations in society and in ways of thinking impose fresh responsibilities on managers. In a world of complexity and change, managers are asked to tackle a much greater diversity of problems. They have to continue to ensure that organizational processes are eâ„cient and that they are served by the latest developments in technology. But this is hardly enough to stay ahead of the game. StaÂ¡ have to be inspired and the organizationâ€™s stock of knowledge captured and distributed, so that the organization learns faster than its competitors. This requires the putting in place of Â£exible structures as well as the demonstration of transformational leadership qualities. Changes in the law and in social expectations require managers to respond positively to eliminate discrimination and to monitor the impact of their organizationsâ€™ activities